Economic Evaluations of Interventions to Optimize Medication Use in Older Adults with Polypharmacy and Multimorbidity: A Systematic Review - Laberge M (Dove Medical Press, 2021)
Maude Laberge,1– 3 Caroline Sirois,2– 5 Carlotta Lunghi,3,6 Myriam Gaudreault,7 Yumiko Nakamura,8 Carolann Bolduc,4 Marie-Laure Laroche9,10 1Department of Operations & Decision Systems, Faculty of Administration, Université Laval, Quebec City, Quebec, Canada; 2Vitam, Centre de recherche en santé durable-Université Laval, Quebec, Canada; 3Centre de recherche du CHU de Québec-Université Laval, Quebec City, Quebec, Canada; 4Faculty of Pharmacy, Université Laval, Quebec City, Quebec, Canada; 5Institut National de santé publique du Québec, Quebec City, Quebec, Canada; 6Department of Health Sciences, Université du Québec à Rimouski, Rimouski, Quebec, Canada; 7Faculty of Administration, Université Laval, Quebec City, Quebec, Canada; 8College of Medicine, University of Florida, Gainesville, FL, USA; 9Centre de Pharmacovigilance, de Pharmacoépidémiologie et d’information sur les médicaments, Service de Pharmacologie, Toxicologie et Pharmacovigilance, CHU de Limoges, Limoges, France; 10Laboratoire Vie-Santé, Faculté de Médecine, Université de Limoges, Limoges, FranceCorrespondence: Maude LabergeDepartment of Operations & Decision Systems, Faculty of Administration, Université Laval, 2325 rue de la Terrasse, Bureau 2519, Quebec City, Québec, G1V 0A6, CanadaTel +1 418-656-2131 ext 407670Fax +1 418-656-2180Email Maude.laberge@fsa.ulaval.caPurpose: To conduct a systematic review of the economic impact of interventions intended at optimizing medication use in older adults with multimorbidity and polypharmacy.Methods: We searched Ovid-Medline, Embase, CINAHL, Ageline, Cochrane, and Web of Science, for articles published between 2004 and 2020 that studied older adults with multimorbidity and polypharmacy. The intervention studied had to be aimed at optimizing medication use and present results on costs.Results: Out of 3,871 studies identified by the search strategy, eleven studies were included. The interventions involved different provider types, with a majority described as a multidisciplinary team involving a pharmacist and a general practitioner, in the decision-making process. Interventions were generally associated with a reduction in medication expenditure. The benefits of the intervention in terms of clinical outcomes remain limited. Five studies were cost-benefit analyses, which had a net benefit that was either null or positive. Cost-utility and cost-effectiveness analyses resulted in incremental cost-effectiveness ratios that were generally within the willingness-to-pay thresholds of the countries in which the studies were conducted. However, the quality of the studies was generally low. Omission of key cost elements of economic evaluations, including intervention cost and payer perspective, limited interpretability.Conclusion: Interventions to optimize medication use may provide benefits that outweigh their implementation costs, but the evidence remains limited. There is a need to identify and address barriers to the scaling-up of such interventions, starting with the current incentive structures for pharmacists, physicians, and patients.Keywords: polypharmacy, economic evaluation, potentially inappropriate medication, cost-effectiveness, cost-utility, cost-benefit